Assessment of the Family History of Patients With Ulcerative Colitis at a Single Center in Japan. Issue 5 (November 2016) - Fujii, Tohru; Sato, Masamichi; Hosoi, Kenji; Ohbayashi, Naho; Ikuse, Tamaki; Jimbo, Keisuke; Aoyagi, Yo; Kudo, Takahiro; Ohtsuka, Yoshikazu; Shimizu, Toshiaki
ABSTRACT: Objectives: The prevalence of ulcerative colitis (UC) differs by country, which is likely due to differences in genetic factors among ethnicities. Moreover, the prevalence of pediatric UC with a family history (FH) is 4.1% in Japanese patients; its clinical course begins at an early age and is more severe. Recently, a genome-wide association study identified 3 new susceptibility loci for adult Japanese patients with UC. Methods: To assess the effects of FH in patients with UC, 60 children were enrolled. Age at diagnosis, clinical features of the initial symptoms, and family structure were assessed in patients with and without an FH. The 3 new loci were examined in patients who provided informed consent. Results: Of the patients with UC, 10 (16.7%) had an FH involving first-degree relatives, including 7 mothers, 1 father, and 2 sisters. There was a trend toward a younger age at onset in the positive FH group. There were, however, no significant differences in the clinical characteristics of the patients regardless of FH. From the genomic analyses, there were significant differences in the polymorphisms of the solute carrier family 26, member 3 (SLC26A3) between those with and without an FH. Conclusions: Although the etiology of UC remains unknown, there were no observed relation between clinical symptoms and FH. SLC26A3 may, however, contribute to the pathogenesis of UC in Japanese individuals with an FH.